Strategi Pengelolaan Pertambangan Pasir Berkelanjutan di Desa Luragung Landeuh, Kuningan, Jawa Barat - Wina Waniatri; Muslihudin; Sri Lestari (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2022)
Most of the mining activities do not have a business license. This condition has been legally handled in court, but many have not taken firm legal action. There is no legal action yet because the implementation of government policies has not been carried out optimally (Ismail, 2007). One of the mining locations in Kuningan Regency is in Luragung Landeuh Village. This study was conducted to determine the sand mining management strategy that should be carried out in Lurangung Landeuh Village, Luragung District, Kuningan Regency. This study uses qualitative and quantitative descriptive analysis methods. The conclusion of this study is the management strategy of sand mining activities in Luragung Landeuh Village based on the results of the highest pairwise comparison assessment or the main priority at the criterion level is environmental and infrastructure sustainability (0.521) and the main priority at the alternative level is tax and environmental insurance (0.199). preserving the environment and infrastructure, which needs to be improved for the convenience of the community, the preservation of flora and fauna, and environmental ecosystems as well as the need for good cooperation between stakeholders and agencies related to the formation of CSR to improve the welfare of the community.